Challenges to human rabies elimination highlighted following a rabies outbreak in bovines and a human in Punjab, India. (18th February 2019) - Brookes, Victoria J.; Gill, Gurlal S.; Singh, Balbir B.; Sandhu, Bhupinder S.; Dhand, Navneet K.; Aulakh, Rabinder S.; Ward, Michael P.
Abstract: In August 2015, a rabies outbreak occurred in bovines in a Punjab village, India; subsequently, a farmer in the same village died of rabies in October 2015. We surveyed farmers to describe the outbreak, the demographics and rabies prophylaxis administered to householders on case farms, and farmers' knowledge of rabies prevention and treatment. We used multiple correspondence analysis to guide investigation of associations between demographics, farm status and rabies knowledge, attitudes and practices. The number of affected bovines was unusually high; 15 cattle and buffalo died on 13 smallholder farms (attack rate 4%). Post‐exposure vaccinations were administered to 24 people (median 2 doses). Affected farms had significantly larger households and were more likely to keep their livestock outside (therefore, accessible by stray dogs), suggesting that the impact of the outbreak was disproportionally borne by households of lower socio‐economic status. Primary sources of rabies information were friends and neighbours, not health authorities or media. Women who had not received formal education were less likely to have heard of rabies. Although case farm participants were more likely to have heard about rabies from a veterinarian, their knowledge and practices to prevent rabies did not reflect the level expected considering their contact with a health professional; they were more likely to believe that traditional remedies prevent rabies and less likely to tell their children to avoid playing with stray dogs than participants from other farms. This study highlights knowledge dissemination disparities that, if typical of rural locations, could obstruct attempts to eliminate canine‐mediated human rabies in India. Therefore, understanding the pervasiveness and influence of traditional medical beliefs on treatment‐seeking behaviour, communication structures within villages and the impact of local practices such as carcass disposal on dog populations will be essential to ensure that rabies control strategies are effective in rural India.